The Impact Of An-nadhar Al-maslahi Of Nawazil Of Coronavirus: Maqasidiyyah Study In The Fatwas Of The Fiqh Councils In Bab Of ‘ibadat - Muneer Ali Abdul Rab; Baidar Mohammed Mohammed Hasan; Mesbahul Hoque (Usuli Faqih Research Centre PLT, 2024)
Indexed by MyCite